Migrant, Roma and Post-Colonial Youth in Education across Europe Being'Visibly Different' - Szalai, Julia; Schiff, Claire; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book compares the educational experiences of adolescents from a variety of'visible' ethnic minority groups across Europe. Focusing on underprivileged urban contexts, it reveals the structural inequalities, as well as the often conflicting inter-ethnic relations which develop in classrooms, playgrounds and larger communities.
Keywords: Science; Science; Science, general